2016
DOI: 10.1016/j.socscimed.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Region of origin diversity in immigrant health: Moving beyond the Mexican case

Abstract: Research suggests that Mexican immigrants arrive in the United States with equivalent or better health than native-born whites but lose their advantage over time. We seek to examine systematically how well the patterns of initial advantage and deteriorating health apply to immigrants originating from other regions of the world – regions that represent a growing proportion of U.S. immigrants. We begin by identifying which of the groups in our study have a health advantage compared to U.S.-born whites and to Mex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…This finding contributes to a growing literature that challenges the applicability of the “epidemiologic paradox” to functional health outcomes (Hummer and Hayward, 2015, Mehta and Elo, 2012). Further, it suggests that theoretical frameworks on immigrant health may not apply equally to immigrants from diverse world regions (Reynolds et al, 2016). Our results also mirrored prior studies that document poorer health among foreign-born Arab Americans relative to the native-born, but have not considered potential variation among arrival cohorts (Dallo et al, 2009, Dallo et al, 2015, Dallo and Kindratt, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding contributes to a growing literature that challenges the applicability of the “epidemiologic paradox” to functional health outcomes (Hummer and Hayward, 2015, Mehta and Elo, 2012). Further, it suggests that theoretical frameworks on immigrant health may not apply equally to immigrants from diverse world regions (Reynolds et al, 2016). Our results also mirrored prior studies that document poorer health among foreign-born Arab Americans relative to the native-born, but have not considered potential variation among arrival cohorts (Dallo et al, 2009, Dallo et al, 2015, Dallo and Kindratt, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The geographic origins of the foreign-born population have become increasingly diverse in recent decades and shifted attention to the importance of region of birth and period of arrival for understanding health outcomes among U.S. immigrants. Studies that once documented consistent patterns of better health on arrival with declining health over time (i.e., the healthy immigrant effect), now find much more varied health trajectories among U.S. immigrants when they are disaggregated by region of birth and arrival cohort (Reynolds, Chernenko, & Read, 2016). Varying levels of economic development and political stability in the sending region, coupled with unique historical relations with the U.S., has contributed to more wide-ranging socioeconomic and health profiles among immigrants from different regions of birth (Almeida, Biello, Pedraza, Wintner, & Viruell-Fuentes, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although this research originated in studies of Hispanic migrants, researchers have also found evidence supporting the "immigrant health advantage" for Asian and Pacific Islander immigrants (Frisbie, Cho, & Hummer, 2001), West Indian and African blacks (Hamilton & Hummer, 2011;, and other immigrant populations (Singh & Hiatt, 2006;. However, scholars have also found considerable heterogeneity within pan-ethnic Hispanic and Asian categories (Camacho-Rivera, Kawachi, Bennett, & Subramanian, 2015;John, de Castro, Martin, Duran, & Takeuchi, 2012;Subramanian, Jun, Kawachi, & Wright, 2009), as well differing trends for immigrant populations that have received less empirical attention, such as Arab and Middle Eastern immigrants (Abdulrahim & Baker, 2009;Reynolds, Chernenko, & Read, 2016). Such variation raises questions about the generalizability of the mechanisms involved in the immigrant health paradox in relation to group-specific and context-specific social conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Age-related differences in the mortality advantage of Hispanic subgroups may reflect either differences in the determinants of mortality by age or differences in selection mechanisms across migration cohorts. Given that the large majority of the foreign born in the US arrived as immigrants prior to age 40 ( Holmes, Driscoll, & Heron, 2015 ), age variation in mortality experience may reflect differences in migrant selection across migration cohorts ( Reynolds, Chernenko, & Read, 2016 ). We may expect greater health selection among migrants prior to the large immigration wave of the 1990s, given less strong migration networks and streams.…”
Section: Introductionmentioning
confidence: 99%